PERANAN PEMBERDAYAAN MASYARAKAT DALAM PENINGKATAN MUTU PEMBANGUNAN - DIAN GUSTRAZAIMAN PURBA TAMBAK (LP2MTBM MAKARIOZ, 2019)
This paper aims to determine the existence of community development in improving development, through the library research method. From the discussion it can be concluded that the empowerment of the community in improving development can provide optimal direction and achievement of community development goals and objectives. Directly directed as a basis for controlling and evaluating the level of success